Consequences of the New UK Tax Exemption System: Evidence from Micro‐level Data. (23rd January 2015) - Egger, Peter; Merlo, Valeria; Ruf, Martin; Wamser, Georg
Abstract : Until 2009, the UK operated a system of worldwide taxation. Under this system, taxation of foreign income was deferred until repatriated as dividends, leaving UK‐owned multinational firms the possibility of avoiding UK taxation by delaying dividend payments and keeping earnings abroad. In 2009, the UK switched to a system under which all foreign‐earned income is exempted from taxation. We evaluate the effects of this reform on foreign affiliates of UK multinationals. Using an identification approach that quasi‐randomises over the country of residence of the ultimate firm owners, we find that the reform significantly affected short‐run repatriation behaviour.